Peningkatan Kualitas Pelayanan Petugas Melalui Implementasi Budaya 5S di UPTD Puskesmas Linggarjati - Silvi Laela Komala Sari; Alfiani Rizqi; M. Ikhsan Prawira Negara; Rizal Zam’an (Universitas Pahlawan Tuanku Tambusai, 2026)
Community health centers (Puskesmas) serve as frontline healthcare facilities that interact directly with the public; consequently, the quality of service provided influences public trust in government health institutions. This community service initiative aimed to enhance service quality at the Linggarjati Community Health Center (UPTD Puskesmas Linggarjati) and thereby increase patient satisfaction. The activities involved interpersonal communication with staff, the use of leaflets covering excellent service and the 5S methodology, and the creation of 5S-themed posters and banners to deepen staff understanding of how these concepts improve service quality. The results demonstrated an increase in patient satisfaction from 73.0% to 87.6%—a rise of 14.6 percentage points. Thus, the implementation of the 5S culture proved effective in improving service quality at the center. These efforts are expected to foster a service culture that is professional, humane, and patient-satisfaction-oriented, ensuring continued improvement in the quality of healthcare services at the Linggarjati Community Health Center.